PENGARUH ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE MEREK SAMSUNG (STUDI DI KOTA SAMARINDA) - Sarwo Eddy Wibowo3, Zamrotul Khoiriyah1, Eddy Soegiarto2 (EKONOMIA, 2016)
The rapid development of technology and information, the individual needs to communicate with other people via mobile phones or mobile phones are not only limited by phone or message. Smartphone comes with more advanced features, is a product of the most popular throughout in 2014. One smartphone manufacturers, namely Samsung achieved the Top Brand Award after experiencing an increase in sales over the last few years. This indicates that Samsung is able to enhance the product attributes such as branding, packaging, labeling and complementary services to improve consumers' purchasing decisions.Â The aim of this study was to determine whether the brand, packaging, labeling and complementary sevices influence the purchasing decision of Samsung smarthpone. The hypothesis stated that the brand, packaging, labeling dan complementary services significantly influence the purchasing decision of Â Samsung smartphone. 100 respondents participated in the study. Data collection method is by using a questionnaire and analyzed by classical assumption test, multiple linear, and hypothesis testing.The analysis showed that the branding, packaging, labeling and complementary services influence the purchasing decisions of Samsung smartphone with a significant value 0.000. T test analysis to examine the effect of branding, packaging, labeling and complementary services to the purchasing decision separately showed the value were 5,097 (X1) 4,049 (X2), 5361 (X3), and -2046 (X4). Product attributes such as branding, packaging and labeling significantly influence the purchasing decision of Samsung smartphone (T arithmetic> T table). While complementary services does not significantly influence the purchasing decision of Samsung smartphone which is indicated by the value (T arithmetic <T table).Â